TI_GERICHTE 11.2014.42 vom 1. September 2014 , Iscrizione provvisoria di ipoteca legale degli artigiani e imprenditori - TI Tribunale d'appello (2014)
Iscrizione provvisoria di ipoteca legale degli artigiani e imprenditori